Effect of material modifier and vibration on mechanical and microstructure properties of aluminium LM6 composite casting - Alhajji, Mohammad Sh I A M I (2021)
Advances in materials such as Metal Matrix Composite (MMC) are rapidly developed due to demands and applications. Reinforced particles of silicon carbide with Al-matrix composites are expected to have many applications in automotive, aircraft, aerospace, and electronics industries due to their enhancement of mechanical properties. Improvement of strength to weight ratio and corrosion resistance still need to be explored in material research activities. Therefore, in this project, the effect of different wt % of Sr on mechanical and microstructure properties of Al-SiC composite + LM6 and the use of copper as corrosion resistance were investigated. For microstructure analysis, the effect strontium was observed, and all samples were characterized on surface morphology by means of SEM equipped with EDS. In addition, the fabrication and identifying the characterizations of aluminium alloy with copper also have been carried out. The amount of copper additions was varied from 0%wt with the intervals of 3%wt for every alloying process. In the process of casting, there were two common types of moulding process; static moulding and vibrating moulding have been carried out. The results showed that the more Sr added, the greater number of alpha dendrites was present and it can clearly be seen. Same as EDS analysis where it also showed that addition of Sr increased the value of Si and Al chemical composition. Next, to fabricate Al-SiC composite, 10 wt % silicon carbide and different percentages (0.02, 0.5) wt % of Al-10Sr was added to LM6 and the particles were mixed by using sand casting vortex method. The addition of different values of Al-10Sr (0.01, 0.02, 0.5) wt % of mechanical properties of Al was also examined. Meanwhile, the analysis results found that UTS for Al increased by adding wt % of Sr and the highest value was 110.23 MPa for Al-0.5 wt % Sr. It was observed that the tensile for the composite did not dramatically increase for each sample. It can be concluded that the weak interface between particles and matrix leads to decreasing UTS value. Strong interface between particles in the matrix showed high strength and stiffness but typically a low resistance to fracture. Moreover, from the analysis of the hardness test on every sample obtained the highest value of Rockwell number was for Al-SiC + 0.5 wt % Sr which was 73.52. This showed that by adding particulate reinforcement of SiC and Sr addition improved the LM6 microstructure and boosted the mechanical properties for better industrial applications especially in automotive and aircraft applications. The fabrication of LM6 alloy with various amounts of copper and using the mechanical vibrations moulding and without vibration moulding was successfully accomplished and the characterizations and mechanical properties of the Al-Si-Cu composite was determined. It was found that the optimum and the best percentage of copper composition in casted LM6 was found to be the 9%wt of copper.